2008
DOI: 10.1016/j.chom.2008.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function of Salmonella SifA Indicate that Its Interactions with SKIP, SseJ, and RhoA Family GTPases Induce Endosomal Tubulation

Abstract: SUMMARY The Salmonella typhimurium type III secretion effector protein SifA is essential for inducing tubulation of the Salmonella phagosome and binds the mammalian kinesin-binding protein SKIP. Co-expression of SifA with the effector SseJ induced tubulation of mammalian cell endosomes, similar to that induced by Salmonella infection. Interestingly, GTP bound RhoA, RhoB, and RhoC also induced endosomal tubulation (ET) when co-expressed with SseJ, indicating that SifA likely mimics or activates a RhoA-family GT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
239
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(253 citation statements)
references
References 34 publications
10
239
2
Order By: Relevance
“…Members of this family were initially suggested to act in some cases by mimicking activated small GTPases [214], but more recent data suggest that they function as GEFs [215]. In fact, the structure of SifA in complex with the PH domain of SKIP revealed that SifA has two distinct domains: the N-terminus binds to SKIP, and the C-terminus has a fold similar to SopE, a Salmonella effector with GEF activity toward Rho GTPases [212]. In addition, SifA can bind to RhoA in human HeLa cells [212], and an interaction of SifA with a Rho GTPase has also been found using the model organism Saccharomyces cerevisiae [216].…”
Section: 5mentioning
confidence: 99%
See 1 more Smart Citation
“…Members of this family were initially suggested to act in some cases by mimicking activated small GTPases [214], but more recent data suggest that they function as GEFs [215]. In fact, the structure of SifA in complex with the PH domain of SKIP revealed that SifA has two distinct domains: the N-terminus binds to SKIP, and the C-terminus has a fold similar to SopE, a Salmonella effector with GEF activity toward Rho GTPases [212]. In addition, SifA can bind to RhoA in human HeLa cells [212], and an interaction of SifA with a Rho GTPase has also been found using the model organism Saccharomyces cerevisiae [216].…”
Section: 5mentioning
confidence: 99%
“…SKIP interacts both with kinesin-1 and SifA via its N-terminal RUN and C-terminal PH domains, respectively. Mammalian proteins SKIP and RhoA form a protein complex with Salmonella effectors SifA and SseJ that promotes host membrane tubulation [212]. In addition, the SifA-SKIP complex plays an essential role in the formation and/or the anterograde movement of PipB2/kinesin-1-positive vesicles that are likely to derive from SCV [213].…”
Section: 5mentioning
confidence: 99%
“…Although detailed insight into these processes is scarce, an emerging theme among effectors is that their enzymatic activity is functionally coupled to their interaction with a particular host factor. For example, SseJ from Salmonella enterica serovar Typhimurium displays glycerophospholipid-cholesterol acyltransferase activity only on binding to the active GTPases RhoA, RhoB, or RhoC (6)(7)(8). Likewise, Pseudomonas aeruginosa ExoU requires mono-or poly-ubiquitinated proteins for the activation of its phospholipase A2 (PLA 2 ) domain (9), whereas Yersinia YpkA exhibits kinase activity only in the presence of host cell actin (10).…”
mentioning
confidence: 99%
“…Transfected SseJ has been shown to localize to and alter lysosomal-associated membrane protein (LAMP)-1-positive membranous compartments independently of additional RhoA expression, and SseJ recruits endogenous activated RhoA to this location upon transfection (5,6). This indicates that the presence of endogenous RhoA in cells is sufficient for SseJ activity on endosomes, which can be measured in transfected SseJ by its ability to cleave the fluorescent phospholipase substrate PEDA1 in HeLa cells (27).…”
Section: Phe106mentioning
confidence: 99%
“…SifA effectively links the vacuole to the microtubule network and motors by binding the host protein SKIP through its amino-terminal domain (4,5). S. typhimurium lacking sifA lose the vacuolar membrane and escape to the cytoplasm, whereas bacteria that lack both sifA and sseJ remain inside the vacuolar membrane, indicating that membrane disruption is dependent upon SseJ (6).…”
mentioning
confidence: 99%